Clinicopathologic study of vascular endothelial growth factor, thrombospondin-1, and microvessel density assessed by CD34 in patients with stage III ovarian carcinoma. (1st January 2006) - Karavasilis, V.; Malamou-Mitsi, V.; Briasoulis, E.; Tsanou, E.; Kitsou, E.; Pavlidis, N.
Abstract : The aim of the study was to investigate angiogenesis in patients with advanced-stage ovarian carcinoma. We used paraffin-embedded tumor tissues from 33 patients diagnosed with FIGO III ovarian cancer who had optimal surgery and received platinum-based chemotherapy. The tissue expression of CD34, vascular endothelial growth factor (VEGF), and thrombospondin-1 (TSP-1) was assessed immunohistochemically. CD34 stained hot spot areas were used to evaluate tumor microvessel density (MVD). VEGF and TSP-1 were assessed by semiquantitative methods. The studied molecules were investigated for relationship with standard clinicopathologic parameters. MVD count was high: median value of 39, range 12–143 microvessels/mm 2 . VEGF was present in all cases and stained strong in 91%. Stroma staining for TSP-1 was weak in 79% of the cases, strong in 6%, and absent in five (15%). We did not find correlations between the three studied markers and histologic type or tumor grade. MVD score did not relate to VEGF or TSP-1. We only observed a trend toward a longer survival in patients with tumors expressing high TSP-1 (60 vs. 36 months, P = 0.1). Proangiogenetic factor VEGF is highly expressed in advanced-stage ovarian carcinomas. The findings of this study may offer support for considering VEGF-targeted therapeutics in ovarian cancer treatment research.